Editorial - Bintliff, John (Journal of Greek Archaeology, 2023)
Our volume opens on a very sad note, the sudden passing of that great scholar of Greek Art, Andrew Stewart (1948-2023). A scholar of immense knowledge and energy, Andy was also greatly loved and admired by his students as well as innumerable colleagues in international scholarship. He supported this Journal from its creation, peer-reviewed papers, contributed his own pathbreaking articles, and encouraged others to successfully offer their work to us. Over many books and papers he gave us unique insights into Greek artistic culture, a contribution to the field which is irreplaceable. This volume is dedicated to him, while our first article is an appreciation by his close friend and colleague Tonio Hölscher. Later in this volume the article by Maria Panagiotonakou is also dedicated to Andy’s memory.